2004
DOI: 10.1002/glia.20110
|View full text |Cite
|
Sign up to set email alerts
|

The cytokine IL‐1β transiently enhances P2X7 receptor expression and function in human astrocytes

Abstract: Extracellular nucleotide di-and triphosphates such as ATP and ADP mediate their effects through purinergic P2 receptors belonging to either the metabotropic P2Y or the ionotropic P2X receptor family. The P2X 7 R is a unique member of the P2X family, which forms a pore in response to ligand stimulation, regulating cell permeability, cytokine release, and/or apoptosis. This receptor is also unique in that its affinity for the ligand benzoyl-benzoyl ATP (BzATP) is at least 10-fold greater than that of ATP. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
147
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 178 publications
(161 citation statements)
references
References 66 publications
8
147
2
1
Order By: Relevance
“…Given that Rac is primarily involved in lamelipodia protrusion at the leading edge (Bokoch, 2005;Barber and Welch, 2006), reduced activity of P2Y 1 R is expected to attenuate cell migration. Clearly, further studies are necessary to evaluate such hypothesis and to elucidate whether the deactivating effect of IL-1β on Rho GTPase seen in mature astrocytes (John et al, 2004) is also effective in reducing astrocyte progenitor cell migration, independently of P2Y 1 R. Nevertheless, because the effects of IL-1β on the activity of P2 receptors reported in the present study are very similar to what has been previously reported for mature astrocytes, i.e., decreased response to agonists of P2Y 1 receptors (Scemes, 2008) and increased response of P2X 7 receptors (Narcisse et al, 2005), it is likely that astrocyte progenitors acquire in early stages of CNS development, the ability to fully respond to IL-1β.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Given that Rac is primarily involved in lamelipodia protrusion at the leading edge (Bokoch, 2005;Barber and Welch, 2006), reduced activity of P2Y 1 R is expected to attenuate cell migration. Clearly, further studies are necessary to evaluate such hypothesis and to elucidate whether the deactivating effect of IL-1β on Rho GTPase seen in mature astrocytes (John et al, 2004) is also effective in reducing astrocyte progenitor cell migration, independently of P2Y 1 R. Nevertheless, because the effects of IL-1β on the activity of P2 receptors reported in the present study are very similar to what has been previously reported for mature astrocytes, i.e., decreased response to agonists of P2Y 1 receptors (Scemes, 2008) and increased response of P2X 7 receptors (Narcisse et al, 2005), it is likely that astrocyte progenitors acquire in early stages of CNS development, the ability to fully respond to IL-1β.…”
Section: Discussionsupporting
confidence: 82%
“…This is based on our current and previous studies showing that neither the P2X 7 R agonist BzATP (this study) nor its antagonist KN-62 (Scemes et al, 2003) had an impact on progenitor cell migration. Although the P2X 7 receptors have been proposed to be a component of the inflammatory response in astrocytes (Narcisse et al, 2005), and a contributor to pathogenic Ca 2+ entry (Yeung et al, 2006), and cell death (Zhang et al, 2005;Wang et al, 2004), further studies are needed to disclose the impact of these ionotropic receptors on neural progenitor cell (patho) physiology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a recent study performed on two P2X 7 Ϫ/Ϫ mouse lines indicated that, at least in the hippocampus of healthy mouse brains, these receptors are either not expressed or are expressed at undetectable levels (Sim et al, 2004), suggesting that they are unlikely candidates for gliotransmitter release under physiological situations. In contrast, under pathological conditions such as during inflammation, ischemia, spreading depression, and trauma, when upregulation of these receptors, changes in extracellular cation composition, and increased extracellular ATP levels have been reported (Kraig and Nicholson, 1978;Harris and Symon, 1984;Nilsson et al, 1993;Le Feuvre et al, 2002;Guerra et al, 2003;Narcisse et al, 2005), the participation of P2X 7 R might be expected to exacerbate the extent of cell damage. Indeed, evidence for the participation of P2X 7 R in the regulation of extracellular transmitter levels was provided from studies showing that ATP-evoked glutamate efflux from neuronal and non-neuronal cells was greatly attenuated in P2X 7 R-null hippocampal slices (Papp et al, 2004) and from those showing that P2X 7 R antagonists greatly attenuated the extent of cell damage after acute spinal cord traumatic injury (Wang et al, 2004).…”
Section: Discussionmentioning
confidence: 94%
“…Additional studies are needed to examine whether expression of P2X7 is regulated and how such regulation might contribute to bone cell function. In this regard, exposure to certain stimuli has been found to enhance P2X7 expression in various cell types [89][90][91]. On the other hand, high concentrations of ATP appear to mediate internalization of P2X7 in osteoclast-like cells [59].…”
Section: Prospects and Conclusionmentioning
confidence: 99%